The Effects of Coaching Strategies for Primary Prevention of Coronary Heart Disease Involving Asymptomatic Hospital Employees - Moreno, Gabriel Mario (CORE Scholar, 2009)
Introduction: An effective coronary heart disease (CHD) prevention program is needed. Currently, prevention of CHD is being sought through pre-CHD risk stratification of patients using office-based screening tools such as the Framingham risk model (Greenland, Smith, and Grundy, 2001). However, patients who are given recommendations for lifestyle behavior modification find difficulty employing and sustaining the changes. The recent popularity of coaching for health behavior change has prompted the question of whether coaching is an effective method to produce a higher success rate for lowering cardiovascular disease following risk stratification. The main purpose of this study was to investigate the effectiveness of a lifestyle counseling program by phone on coronary heart disease risk in a working population with elevated CHD risk factors. Methods: The study utilized a randomized controlled trial in which a group of fifty full-time hospital employees (n=54) participated in risk stratification for CHD and subsequently received access to the hospital's Wellness Center and information regarding the therapeutic lifestyle changes (TLC) recommended by the National Cholesterol Education Program (Executive summary of the third report of the national cholesterol education program (NCEP) expert panel on detection, evaluation, and treatment of high blood cholesterol in adults (adult treatment panel III).2001) Twenty-seven subjects received a wellness coach and twenty-seven subjects served as controls. All measurements were performed at week zero to provide baseline data and week seventeen to provide post-study data. The measurements performed included height, weight, blood pressure, activity monitoring accessed via an accelerometer. In addition, blood sampling was in week zero and week seventeen to assess serum levels of fasting glucose, very-low-density lipoprotein (VLDL), low-density lipoprotein (LDL), high-density lipoprotein (HDL), total cholesterol (TC), and triglycerides (TG). Lastly, a Well-being Assessment (WBA) from Wellcoaches Inc., completed in week zero and week seventeen identified each participant's pre- and post-intervention perception of self-efficacy and motivation concerning the areas of nutrition, exercise, and stress. Results: There were no significant results from the between group comparison. Conclusion: Individuals in both groups experienced beneficial risk factor outcomes. However, the outcomes of the coached group were not significantly difference from that of the control group. Adherence to the coaching program was a major obstacle in evaluating its effectiveness.